Shallow sub-lakes are essential for sustaining the successful wintering of waterbirds in Poyang Lake, China - Mengjie Lu; Zhen Zhang; Peng Chen; Changxin Xu; Bin Gao; Luzhang Ruan (Avian Research)
For migratory waterbirds, the quality of wintering habitat is related to spring migration and successful breeding in the next year. The availability of food resources in the habitat is critical and varies within water levels. Although the water-level fluctuations in Poyang Lake have been extremely variable interannually in recent years, the wintering waterbird populations have remained relatively stable. Hence, the mechanism of maintaining the stability is worth exploring. This study aimed to compare the distribution of vegetation and herbivorous waterbirds in 2015–2016 and 2016–2017, focusing on three shallow sub-lakes and one main lake are. The results showed that the emergence of tubers and the growth of Carex spp. provided a continuous food supply and habitat for wintering waterbirds with a gradual decline in the water level. Shallow sub-lakes supported almost all of the tuber-eating waterbirds (1.42–1.62 × 105) and most geese (1.34–1.53 × 106). However, the main lake area, covered with Persicaria hydropiper, did not provide adequate and accessible food. This resulted in almost no distribution of tuber-eating waterbirds, with only a few geese congregating in early winter. Our results demonstrated that the shallow sub-lakes under human control provided a different environment from the main lake and are key to sustaining the successful wintering of hundreds of thousands of migratory waterbirds in Poyang Lake. Therefore, we recommend refining the anthropogenic management of the shallow sub-lakes to regulate the water level to ensure the carrying capacity of Poyang Lake.